2016
DOI: 10.1002/cncr.30118
|View full text |Cite
|
Sign up to set email alerts
|

Breast intraductal papillomas without atypia in radiologic‐pathologic concordant core‐needle biopsies: Rate of upgrade to carcinoma at excision

Abstract: Background The surgical management of breast intraductal papilloma without atypia (IDP) identified at core needle biopsy (CNB) is controversial. We assessed the rate of upgrade to carcinoma at surgical excision, and identified parameters predictive of upgrade. Methods We identified women with CNB diagnosis of intraductal papilloma without atypia or carcinoma at our center between 2003 and 2013. Radiologic-pathologic concordance was assessed for all cases, and discordant cases were excluded. We correlated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 34 publications
11
70
1
Order By: Relevance
“…In previous studies, the upgrade rate was substantially lower in cases with pathologic-radiologic concordance [6,7]. In the present study, 2 patients with IDP and subsequent upgrade after excision showed initial BI-RADS 5, indicating pathologic-radiologic discordance after initial biopsy.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In previous studies, the upgrade rate was substantially lower in cases with pathologic-radiologic concordance [6,7]. In the present study, 2 patients with IDP and subsequent upgrade after excision showed initial BI-RADS 5, indicating pathologic-radiologic discordance after initial biopsy.…”
Section: Discussionmentioning
confidence: 51%
“…Many investigators suggested that areas of atypia or carcinoma may be missed in the limited tissue material gained with needle biopsy, thus requiring excisional biopsy for IDPs. Meanwhile, others suggested that IDPs with concordant benign imaging characteristics do not require excision [6,17,18]. To our knowledge, almost all previous studies investigated IDP based on only a single imaging modality with a focus on US [19], while our study evaluated both CNB and VAB guided by MG, US, and MRI.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations